Initial consonant replacement in Classical Manx - Broderick, George (Studia Celtica, 2019)
In his Sir John Rhŷs Memorial Lecture of 1969 Robert L. Thomson provided a detailed analysis of initial consonant replacement in the Classical Manx of the eighteenth century, in which he was able to set out the use or non-use of such replacement by various authors of that century. - However, Thomson's presentation of the material is not easy to digest today, and in order to facilitate an easier understanding of the importance of these developments, the material has here been repackaged and presented anew.
Gesehen am 21.08.2024